Copper(I)-catalyzed tandem reaction: synthesis of 1,4-disubstituted 1,2,3-triazoles from alkyl diacyl peroxides, azidotrimethylsilane, and alkynes - Israr, Muhammad; Ye, Changqing; Muhammad, Munira Taj; Li, Yajun; Bao, Hongli (Beilstein Journal of Organic Chemistry, 2018)
A copper-catalyzed azide–alkyne cycloaddition (CuAAC) reaction for the synthesis of 1,4-disubstituted 1,2,3-triazoles from alkyl diacyl peroxides, azidotrimethylsilane, and terminal alkynes is reported. The alkyl carboxylic acids is for the first time being used as the alkyl azide precursors in the form of alkyl diacyl peroxides. This method avoids the necessity to handle organic azides, as they are generated in situ, making this protocol operationally simple. The Cu(I) catalyst not only participates in the alkyl diacyl peroxides decomposition to afford alkyl azides but also catalyzes the subsequent CuAAC reaction to produce the 1,2,3-triazoles.
Keywords: alkyl diacyl peroxides; azidotrimethylsilane; click reaction; copper catalysis; radical; 1,2,3-triazoles

(untitled) - Kolb, H. C.; Finn, M. G.; Sharpless, K. B. (Angew. Chem., Int. Ed., 2001)

(untitled) - Wang, Q.; Chan, T. R.; Hilgraf, R.; Fokin, V. V.; Sharpless, K. B.; Finn, M. G. (J. Am. Chem. Soc., 2003)

(untitled) - Ustinov, A. V.; Stepanova, I. A.; Dubnyakova, V. V.; Zatsepin, T. S.; Nozhevnikova, E. V.; Korshun, V. A. (Russ. J. Bioorg. Chem., 2010)

(untitled) - Speers, A. E.; Adam, G. C.; Cravatt, B. F. (J. Am. Chem. Soc., 2003)

(untitled) - Nair, D. P.; Podgórski, M.; Chatani, S.; Gong, T.; Xi, W.; Fenoli, C. R.; Bowman, C. N. (Chem. Mater., 2014)

(untitled) - Moses, J. E.; Moorhouse, A. D. (Chem. Soc. Rev., 2007)

(untitled) - Link, A. J.; Tirrell, D. A. (J. Am. Chem. Soc., 2003)

(untitled) - Kolb, H. C.; Sharpless, K. B. (Drug Discovery Today, 2003)

(untitled) - Hein, C. D.; Liu, X.-M.; Wang, D. (Pharm. Res., 2008)

(untitled) - El-Sagheer, A. H.; Brown, T. (Chem. Soc. Rev., 2010)

(untitled) - Deiters, A.; Cropp, T. A.; Mukherji, M.; Chin, J. W.; Anderson, J. C.; Schultz, P. G. (J. Am. Chem. Soc., 2003)

(untitled) - Amblard, F.; Cho, J. H.; Schinazi, R. F. (Chem. Rev., 2009)

(untitled) - Tornøe, C. W.; Christensen, C.; Meldal, M. (J. Org. Chem., 2002)

(untitled) - Rostovtsev, V. V.; Green, L. G.; Fokin, V. V.; Sharpless, K. B. (Angew. Chem., Int. Ed., 2002)

(untitled) - Meldal, M.; Tornøe, C. W. (Chem. Rev., 2008)

(untitled) - Hein, J. E.; Fokin, V. V. (Chem. Soc. Rev., 2010)

(untitled) - Liang, L.; Astruc, D. (Coord. Chem. Rev., 2011)

(untitled) - Sokolova, N. V.; Nenajdenko, V. G. (RSC Adv., 2013)

(untitled) - Haldón, E.; Nicasio, M. C.; Pérez, P. J. (Org. Biomol. Chem., 2015)

(untitled) - Wei, F.; Wang, W.; Ma, Y.; Tung, C.-H.; Xu, Z. (Chem. Commun., 2016)

(untitled) - Johansson, J. R.; Beke-Somfai, T.; Said Stålsmeden, A.; Kann, N. (Chem. Rev., 2016)

1,3-Dipolar Cycloaddition Chemistry - Huisgen, R. (Chapter 1, 1984)

Organic Azides: Syntheses and Applications - Bräse, S.; Banert, K. (John Wiley & Sons, 2010)

(untitled) - Odlo, K.; Høydahl, E. A.; Hansen, T. V. (Tetrahedron Lett., 2007)

(untitled) - Liang, X.; Andersen, J.; Bolvig, S. (Synlett, 2005)

(untitled) - Kacprzak, K. (Synlett, 2005)

(untitled) - Feldman, A. K.; Colasson, B.; Fokin, V. V. (Org. Lett., 2004)

(untitled) - Quan, Z.-J.; Xu, Q.; Zhang, Z.; Da, Y.-X.; Wang, X.-C. (J. Heterocycl. Chem., 2015)

(untitled) - Tao, C.-Z.; Cui, X.; Li, J.; Liu, A.-X.; Liu, L.; Guo, Q.-X. (Tetrahedron Lett., 2007)

(untitled) - Hao, C.; Zhou, C.; Xie, J.; Zhang, J.; Liu, P.; Dai, B. (Chin. J. Chem., 2015)

(untitled) - Chen, B.; Yang, D.; Fu, N.; Liu, Z.; Li, Y. (Synlett, 2007)

(untitled) - Partyka, D. V.; Updegraff, J. B.; Zeller, M.; Hunter, A. D.; Gray, T. G. (Organometallics, 2007)

(untitled) - Taherpour, A. A.; Kheradmand, K. (J. Heterocycl. Chem., 2009)

(untitled) - Saha, S.; Kaur, M.; Bera, J. K. (Organometallics, 2015)

(untitled) - Carmona, A. T.; Carrión-Jiménez, S.; Pingitore, V.; Moreno-Clavijo, E.; Robina, I.; Moreno-Vargas, A. J. (Eur. J. Med. Chem., 2018)

(untitled) - Kolarovič, A.; Schnürch, M.; Mihovilovic, M. D. (J. Org. Chem., 2011)

(untitled) - Li, Y.; Han, Y.; Xiong, H.; Zhu, N.; Qian, B.; Ye, C.; Kantchev, E. A. B.; Bao, H. (Org. Lett., 2016)

(untitled) - Moad, G.; Rizzardo, E.; Solomon, D. H. (Aust. J. Chem., 1983)

(untitled) - Dong, X.; Han, Y.; Yan, F.; Liu, Q.; Wang, P.; Chen, K.; Li, Y.; Zhao, Z.; Dong, Y.; Liu, H. (Org. Lett., 2016)

(untitled) - Ge, L.; Li, Y.; Jian, W.; Bao, H. (Chem. – Eur. J., 2017)

(untitled) - Ye, C.; Li, Y.; Bao, H. (Adv. Synth. Catal., 2017)

(untitled) - Zhou, H.; Jian, W.; Qian, B.; Ye, C.; Li, D.; Zhou, J.; Bao, H. (Org. Lett., 2017)

(untitled) - Yuan, Y.-A.; Lu, D.-F.; Chen, Y.-R.; Xu, H. (Angew. Chem., Int. Ed., 2016)